Analisis Pengaruh Inflasi, Suku Bunga BI Rate Dan Nilai Tukar Rupiah Terhadap Harga Saham(Studi Empiris Pada Perusahaan Sektor Pertambangan Di BEI 2011-2013) - Kusuma, Franky Pranata Putra, Dra. Wuryaningsih Dwi Lestari, M.M (2015)
This research aims to analyze the effect of partially or simultaneous inflation, interest rate and exchange rate BI rupiah against the stock prices of companies in the mining sector Indonesian Stock Exchange period 2011-2013. This research is quantitative research. The population in this research y 40 mining sector companies in Indonesia stock exchange listing, the method to take is purposive Sampling, retrieved 22 mining sector Companies that meet these criteria. Method of data collection in this research is a method of documentation, i.e. with a noted stock price data each month listed on the Indonesian Capital Market directory (ICDM), the inflation data as well as data rates BI rate and the exchange rate of rupiah which was published by the official website of Bank Indonesia. Data analysis in this study i.e. with descriptive statistics, classic assumption Test that includes a test of normality, multikolonieritas test, heteroskedastisitas test and autocorrelation test, then test the hypothesis that includes multiple linear regression analysis, t-test, f-test and a test of determination. The results of this research the negative effect of inflation is not significantly to the stock price, so his little big inflation does not affect stock prices. BI interest rate positive and significant effect against the share price it is clear that an increase in interest rates on the BI Rate will be followed by an increase in the stock price. Then the exchange rate of the Indonesian Monetary Unit is negative and significant effect against the stock price, so an increase in the exchange rate of the rupiah against the U.S. dollar will lower the price of the stock. Simultaneous inflation, interest rate and exchange rate BI rupiah effect significantly to the company's mining sector's share price in the period 2011-2013 Indonesian Stock Exchange.